A switching system approach to sensor and actuator assignment for stabilisation via limited multi-packet transmitting channels - Guo, Ge (International journal of control, 2011)
The problem of joint design of dynamic output feedback controller and network access assignment sequences of both input and output channels is investigated for networked control systems which have insufficient communication channels to simultaneously accommodate all the sensors and actuators. The sensors and the actuators are supposed to operate independently with individual communication packets and subject to successive time-varying delays and packet dropouts. A linear matrix inequality-based design method for dynamic output feedback controllers that are asymptotically stabilising and less conservative is derived using a model transformation technique and an improved Lyapunov-Krasovskii function. At the same time, a switching rule for assigning communication channels among the sensors and actuators while guaranteeing that the closed-loop system is asymptotically stable is suggested in the framework of switching system theory. Numerical examples are provided to show the usefulness and efficiency of the developed control and communication sequence design method.